A Real-World Study of Cetylated Fatty Acids Food Supplement Administration in Italian Adults for Sub-Acute or Chronic Musculoskeletal Pain - Lanzisera R; Gervasoni F; Rossato MS; Tarantino G; Lo Mauro A; Geri E (Journal of Pain Research)
Rosaria Lanzisera,1 Fabrizio Gervasoni,2 Maria Sole Rossato,3 Germano Tarantino,3 Antonella Lo Mauro,4 Elisabetta Geri1 1UOC Recupero E Riabilitazione Funzionale, Ambito Territoriale Pisano, ASL Toscana Nordovest, Pisa, Italy; 2ASST Fatebenefratelli Sacco, Milan, Italy; 3PharmaNutra S.p.A., Pisa, Italy; 4Dipartimento di Elettronica, Informazione e Bioingegneria, Politecnico di Milano, Milan, ItalyCorrespondence: Maria Sole Rossato, Email ms.rossato@pharmanutra.itPurpose: This real-world observational study was conducted to evaluate decrease in pain after 30-day administration of a new oral cetylated fatty acids (CFA) food supplement, assess if decreased pain resulted in a lower consumption of oral non-steroidal anti-inflammatory drugs (NSAIDs), and improvement in related gastric side effects. It was the first study of this food supplement in a real-world setting.Patients and Methods: A hundred and twenty Italian primary care physicians recruited 562 patients who were prescribed oral CFA. Patients completed the Brief Pain Inventory (BPI) questionnaire at baseline and after 30 days of dosing. Their CFA intake adherence and use of NSAIDs were recorded. All analyses were done using R statistical software; p-value ≤ 0.005 was considered statistically significant.Results: We analyzed data of 196 males and 366 females aged in an average 49.2 years. After 30 days of CFA intake, we observed a statistically significant reduction (38.84%) in the overall pain score, 44.53% reduction in the interference score in daily activities, relief from pain within the previous 24 hours 47.16 (± 11.44%) at baseline and 62.14 (± 27.93%) after 30 days, and progressive reduction in NSAID intake frequency and total dose over time. More than half of participants (55.2%) reported improvement in gastric side effects typically associated with NSAID use.Conclusion: Data analyses indicated that using the new oral CFA food supplement decreased pain, which helped improve the quality of life, better perform daily activities (interference reduced by 44.5%), and reduce painkiller consumption by 19.7% in terms of both dose and frequency. Half of participants (55.2%) rated NSAID-related hyperchlorhydria and heartburn as improved. Although placebo effect might have contributed, the results suggest that CFA may have a positive effect in patients with sub-acute and chronic musculoskeletal pain and can enhance therapies typically used in this population.Keywords: pain, cetylated fatty acids, quality of life